2008
DOI: 10.1074/jbc.m806143200
|View full text |Cite
|
Sign up to set email alerts
|

IMP Dehydrogenase Type 1 Associates with Polyribosomes Translating Rhodopsin mRNA

Abstract: IMP dehydrogenase (IMPDH) catalyzes the pivotal step in guanine nucleotide biosynthesis. Here we show that both IMPDH type 1 (IMPDH1) and IMPDH type 2 are associated with polyribosomes, suggesting that these housekeeping proteins have an unanticipated role in translation regulation. This interaction is mediated by the subdomain, a region of disputed function that is the site of mutations that cause retinal degeneration. The retinal isoforms of IMPDH1 also associate with polyribosomes. The most common disease-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 54 publications
1
52
0
Order By: Relevance
“…The recent discovery that point mutations in the Bateman domain of IMPDH type 1 cause human retinitis pigmentosa yet confer no detectable catalytic defect reinforced this view, renewed the interest in IMPDH biology, and suggested that further in vivo studies were necessary (14,(33)(34)(35)(36)(37)(38). Having only one gene for IMPDH and being the most easily genetically manipulated system, E. coli seems to be an ideal organism for in vivo studies of IMPDH.…”
Section: Discussionmentioning
confidence: 99%
“…The recent discovery that point mutations in the Bateman domain of IMPDH type 1 cause human retinitis pigmentosa yet confer no detectable catalytic defect reinforced this view, renewed the interest in IMPDH biology, and suggested that further in vivo studies were necessary (14,(33)(34)(35)(36)(37)(38). Having only one gene for IMPDH and being the most easily genetically manipulated system, E. coli seems to be an ideal organism for in vivo studies of IMPDH.…”
Section: Discussionmentioning
confidence: 99%
“…5B). IMPDH can bind RNA and polysomes and has been implicated in selective control of translation (Mortimer et al 2008). Studies in Drosophila showed that IMPDH is also a sequence-specific DNA-binding transcriptional repressor that binds unwound CT-rich regulatory DNA elements ( Fig.…”
Section: Chromatin and Transcription Control By Nucleotide Biosynthetmentioning
confidence: 99%
“…Bateman domains interact with diverse regulatory ligands, including adenosine nucleosides (18), cytoplasmic ions (22), charged membrane domains (23), DNA and RNA (24,25), and other proteins (26). Interactions with regulatory ligands induce Bateman domain conformational changes that control protein function (19,21).…”
Section: Introductionmentioning
confidence: 99%